Studies on temperature characteristics and initial formation interface during cyclopentane-methane hydrate formation in large-scale equipment with bubbling - Cai, Jing; Lv, Tao; Zhang, Yu; von Solms, Nicolas; Xu, Chun-Gang; Chen, Zhao-Yang; Li, Xiao-Sen (Applied Energy, 2020)
In this work, temperature characteristics during hydrate formation were investigated in the cyclopentane-methane system using large-scale equipment with bubbling. The volume in each experiment was increased by a factor of 80 compared with previous work. A group of scaled-up experiments, under the optimal condition based on experiments in the smaller crystallizer, was carried out to verify the scale-up potential of hydrate-based thermal fluid production process. Another group of scaled-up experiments were performed with different variables (volume ratio of cyclopentane to water, gas/liquid ratio and pressure) to figure out the initial hydrate formation interface and optimize the temperature of the thermal fluid. Experimental results illustrate that hydrate-based thermal fluid production process can be scaled up by a factor of 80, however, the temperature of the thermal fluid needs to be optimized by adjusting variables accordingly. Moreover, the liquid cyclopentane/water interface more than the gas/liquid interface affects hydrate formation and hydrate accumulation. In particular, the hydrate formation interface initially occurs on the water side near the liquid cyclopentane/water interface. A large amount of hydrate accumulates in the bulk liquid cyclopentane phase, forming new hydrate formation interfaces. Thermal fluid with a specific temperature range can be produced based on the heat released and conducted from the hydrate formation interfaces.